Suppression of Urinary Voiding by Conditional High Frequency Stimulation of the Pelvic Nerve in Conscious Rats - Brouillard, Charly B. J.; Crook, Jonathan J.; Irazoqui, Pedro P.; Lovick, Thelma A. (Frontiers in Physiology, 2018)
Female Wistar rats were instrumented to record bladder pressure and to stimulate the left pelvic nerve. Repeated voids were induced by continuous infusion of saline into the bladder (11.2ml/h) via a T-piece in the line to the bladder catheter. In each animal tested (n=6) high frequency pelvic nerve stimulation (1-3kHz, 1-2mA sinusoidal waveform for 60s) applied within 2s of the onset of a sharp rise in bladder pressure signaling an imminent void was able to inhibit micturition. Voiding was modulated in three ways: 1. Suppression of voiding (4 rats, n=13 trials). No fluid output or a very small volume of fluid expelled (<15% of the volume expected based on the mean of the previous 2 or 3 voids). Voiding suppressed for the entirety of the stimulation period (60s) and resumed within 37s of stopping stimulation. 2. Void deferred (4 rats, n=6 trials,). The imminent void was suppressed (no fluid expelled) but a void occurred later in the stimulation period (12-44s, mean 24.5±5.2s after the onset of the stimulation). 3. Reduction in voided volume (5 rats, n=20 trials). Voiding took place but the volume of fluid voided was 15-80% (range 21.8-77.8%, mean 45.3±3.6%) of the volume expected from the mean of the preceding 2 or 3 voids. Spontaneous voiding resumed within 5min of stopping stimulation. Stimulation during the filling phase in between voids had no effect. The experiments demonstrate that conditional high frequency stimulation of the pelvic nerve started at the onset of an imminent void can inhibit voiding. The effect was rapidly reversible and was not accompanied by any adverse behavioural side effects.